Institutionalization of Human Rights’ Protection in ASEAN: Commentary to the Terms of Reference for the ASEAN Intergovernmental Commission on Human Rights (AICHR) - A. H. Abashidze; A. M. Solntsev (Московский журнал международного права, 2010)
ASEAN was founded on August 8, 1967. In November 2007, the heads of ASEAN member states took historic steps towards establishing an “ASEAN Community” when they convened in Singapore for the 13th ASEAN Summit. First and foremost, they signed the ASEAN Charter, which provides the organization with a formal legal personality and expands upon its values and institutional mechanisms. Article 14 of the ASEAN Charter provides that “[i]n conformity with the purposes and principles of the ASEAN Charter relating to the promotion and protection of human rights and fundamental freedoms, ASEAN shall establish an ASEAN human rights body” which «shall operate in accordance with the terms of reference to be determined by the ASEAN Foreign Ministers Meeting. The Terms of Reference for the ASEAN Intergovernmental Commission on Human Rights (AICHR) has been adopted on 20th of July, 2009 at the ASEAN Ministerial Meeting. The next step in this long awaited process will be at the upcoming ASEAN 15th Summit, in October of this year, where ASEAN member states will appoint representatives to the body.